Children with Special Needs in Latvia. Legislative Frame - Daniela, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The analysis of the legislative regulation which determines the rights of children with special needs and regulates their guarantee leads to the conclusion that, on the one hand, defining equal rights to all children to receive education but failing to ensure these rights to children with special needs in a place that is as much as possible close to their dwelling place, their rights to live in the family, to choose education that corresponds to their desire as well as the possibility to socialize with children who have no special needs are violated. Why such statements? They are based on the analysis of the legislative acts of the Republic of Latvia and the education possibilities offered by the municipalities.